Теоретичні основи проектно-технологічно-виробничого забезпечення тактико-технічних характеристик бойових броньованих машин - Хлань, Олександр Володимирович; Ткачук, Микола Анатолійович; Грабовський, Андрій Володимирович (НТУ "ХПІ", 2018)
У роботі наведено удосконалення методу узагальненого параметричного моделювання та виготовленні бойових броньованих машин на основі доповнення параметричного простору технологічно-виробничими чинниками. Проведено формування задачі та узагальнення критеріїв при обґрунтуванні технічних рішень для елементів бойових броньованих машин, а також технологічних систем для їх виготовлення. Прийнято до уваги режими бойового застосування та характеристики засобів ураження. Створено узагальнені параметричні моделі досліджуваних елементів бойових броньованих машин. Визначено алгоритм обґрунтування раціанальних технічних рішень на етапах їх проектування, технологічної підготовки виробництва і виготовлення.

The method of generalized parametric modeling and manufacturing of armored fighting vehicles is improved. This improvement is based on the replenishment of the parametric space by technological and production factors. The formation of the task set and the generalization of criteria for just ification of technical solutions for elements of armored fighting vehicles are carried out, as well as technological systems for their manufacture. Regimes of fighting use and characteristics of weapons of destruction are taken into account. Generalized parametric models of investigated elements of armored fighting vehicles are created. An algorithm for substantiating rational technical solutions at the stages of their design, technological preparation of production and manufacturing is defined. The principle for balancing of technical solutions at all life cycle stages of a rmored combat armored vehicles has been developed to formulate recommendations. It provides the achievement of maximum values of minimum level of characteristic at each stage and sub-stages in design, technological preparation of production and production of armored fighting vehicles. In addition, the criterion for parameter justifying is proposed for determination of rational technical solutions that are weakly sensitive to the variation of design parameters.
Theoretical basis for design-technological-production support of tactical and technical characteristics of fighting armored vehicles
Keywords: ББМ; ТТХ; параметричне моделювання; бойове застосування; засіб ураження; технологічна система; parametric modeling; fighting application; means of destruction